Phytochemical Screening and Cytotoxic Effects of Crude Extracts of Pereskia Bleo Leaves - Salleh, Siti Farhanah Mohd; Ismail, Norzila; Ibrahim, Wan Suriyani Wan; Ismail, Tuan Nadrah Naim Tuan (Taylor & Francis, 2020)
The phytocompounds in crude solvent extracts of Pereskia bleo leaves were identified and their cytotoxic effects on cancer cell lines were determined. Crude extracts were obtained via maceration and subjected to GCMS analysis. Then, each extract was incubated with HeLa, MDA-MB-231, SW480, and NIH/3T3 cell lines for 72 h. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was done to determine IC50 values of each extract. Terpenoids, sterols, alkaloids, fatty acids and phenolic compounds were identified from the crude extracts of P. bleo leaves. Other compounds identified were γ-sitosterol, β-tocopherol, and γ-tocopherol. The ethyl acetate extract had potent cytotoxic effect against HeLa and MDA-MB-231 cancer cells as noted by the lowest IC50 values